Executive function impairments in depression and bipolar disorder: association with functional impairment and quality of life - Cotrena, Charles; Branco, Laura Damiani; Shansis, Flávio Milman; Fonseca, Rochele Paz (Journal of affective disorders, 2016)
The neuropsychological correlates of major depressive (MDD) and bipolar disorder (BD), and their association with quality of life (QOL) and functioning, have not been sufficiently studied in the literature. The present study aimed to compare executive functions, attention, processing speed, QOL and disability between patients with BD type I, BD type II, MDD and healthy controls. Method: 205 participants (n=37 BDI, 81% female; n=35 BDII, 80% female; n=45 MDD, 69% female; n=89C, 46% female) aged between 18 and 67 years were administered an extensive neurocognitive battery consisting of widely used standardized measures such as the Trail Making Test, the Stroop Color-Word Test and a modified version of the Wisconsin Card Sorting Task. Z-scores were compared between groups by ANCOVA. The prevalence of impairments on each measure (Z-score<1.5) was compared between groups using chi-square tests. The associations between cognition, quality of life and functioning were evaluated through correlational analysis. Results: Patients with MDD showed poor selective and sustained attention, and exhibited impairments in timed tasks, suggesting low efficiency of executive processing. Patients with BDI displayed more widespread cognitive impairment than the remaining groups, and performed worse than subjects with MDD on measures of sustained attention and inhibitory control. Decision-making ability and attentional control were able to distinguish between patients with BDI and BDII. QOL and disability were most impaired in patients with BDI, and more closely associated with cognitive impairment than in the remaining groups. Limitations: No control of pharmacological variables, clinical or demographic characteristics. Conclusions: Our results provide important information regarding the nature and severity of the cognitive alterations associated with different mood disorders, and may contribute to the diagnosis, rehabilitation and treatment of these conditions. •Patients with MDD showed poor attention, low efficiency of executive processing.•Patients with BDI showed widespread cognitive impairment.•Selective attention and decision making were worse in BDII than BDI.•Disability and QOL were worse in BDI, and more closely related to cognition.•Neuropsychological interventions targeting each mood disorder should be developed.